Pengelolaan Sediaan Obat Pada Logistik Farmasi Rumah Sakit Umum Tipe B di Jawa Timur - Stella Herliantine Febreani; Djazuly Chalidyanto (Universitas Airlangga, 2016)
Inventory control of drugs in hospital which are not done properly can cause stockout or stagnant of supplies. Based of data processing of the drug at Siti Khodijah Sepanjang Hospital experienced stagnant amount 38,9% and stockout amount 29,3% during period January-September 2015. The objectives of the study were to analysis inventory control of drug in logistic pharmacy Siti Khodijah Sepanjang Hospital. This research was a descriptive research with cross sectional design by observation and interviews. Indepth interviews were carried out to get more detailed information about the variables examined. Activity of planning, procurement, distribution, and storage are performed not effective enough so led to stagnant and stockout drug. Also evaluation that has running was not adequate because only looks about financial audit. The conclusion that can be drawn is logistic management system has not run effectively so that the occurrence so stagnant and stockout drug.Keywords: drug stagnant and stockout, hospital, inventory control, logistic management